The Factors Influencing Men to Joining Farmers’ Groups: The Case of Tchenzema Ward Mgeta Division, Mvomero District, Morogoro Region, Tanzania - Daniel Nyoki; Emmanuel G. Rwambali (Archives of Current Research International, 2017)
The study on the factors influencing men to joining farmers’ groups was carried out at Morogoro Region, Tanzania in 2008. The objectives of the study were to identify reasons influencing or hindering men from joining farmers’ groups; and to determine factors that would motivate men to join farmers’ groups. The sample was drawn from the list of male group members of various farmers groups and male non-group members in Tchenzema Ward. A stratified sample was then drawn from the two lists. A sample of 40 respondents was picked using a simple random sampling procedure in each group. Thus, 20 respondents were male group members and 20 non group members. The main findings indicated that all respondents were aware of the existence of farmers’ groups. The observed factors hindering men from joining farmers groups includes: lack of immediate benefits (80%); alcoholism (55%); engagement in other economic activities (52.5%); poor leadership (80%); lack of awareness of group benefits (27.5); avoidance of group entry fee (50%); and some men regarded group work as wastage of time (72.5%). Factors that would motivate and raise participation of men in the farmers groups included: awareness creation about importance of farmers groups; provision of credits to group members; strong and good leadership and provision of rewards for better performing group. It was thus concluded that issues of immediate benefits and good leadership would encourage more men to join the groups. Therefore it was recommended that awareness creation should be based on very clear objectives and preferably done by developmental institutions or agencies.